Expression of MMIF, HIF-1α and VEGF in Serum and Endometrial Tissues of Patients with Endometriosis - Zhang, Fan; Liu, Xiao-ling; Wang, Wan; Dong, Hong-ling; Xia, Yu-fang; Ruan, Li-ping; Liu, Li-ping (Current medical science, 2018)
Summary The aim of this study was to investigate the expression of macrophage migration inhibitory factor (MMIF), hypoxia-inducible factor-1 a (HIF-1α) and vascular endothelial growth factor (VEGF) in the serum and endometrial tissues of patients with endometriosis (EM) and the clinical significance. Eighty EM patients [American Reproductive Association stage I ( n =20), stage II ( n =22), stage III ( n =21) and stage IV ( n =17)] were enrolled and divided into mild (10-14 points, n =28), moderate (16-24 points, n =27) and severe (26-30 points, n =25) dysmenorrhea groups. The control group included 40 healthy women of childbearing age who underwent routine healthcare examinations in the enrolment period. The expression of MMIF, HIF-1α and VEGF in the serum and endometrial tissues was measured by enzyme-linked immunosorbent assay and Western blotting, respectively. Meanwhile, the sensitivity and specificity of serum MMIF, HIF-1α, and VEGF when separately used as single indexes or jointly used as one index were examined as well. The results showed that serum concentrations of MMIF, HIF-1α, and VEGF were significantly higher in EM patients than in controls ( P <0.05). The expression of all three proteins in both serum and endometrial tissues increased significantly with the R-AFS stage ( P <0.05) and with dysmenorrheal severity ( P <0.05). The sensitivity and specificity of the combined detection of serum MMIF, HIF-1α, and VEGF levels were significantly higher than those of single index detection ( P <0.05). In conclusion, the expression of MMIF, HIF-1α, and VEGF in the serum and endometrial tissues may be used to assess the stage of EM and the severity of dysmenorrhea. Combined evaluation of MMIF, HIF-1α, and VEGF significantly improves the diagnostic sensitivity and specificity.